Reforming middle level education : considerations for policymakers - Thompson, Sue Carol, 1946- (Handbook of research in middle level education series., 2004)
This volume of The Handbook of Research in Middle Level Education is a significant contribution to the literature on middle level schools because it is written specifically with policymakers in mind. Middle level scholars have illuminated the most important issues concerning the education of young adolescents of which policymakers must be knowledgeable. It is only by having informed policymakers that middle level schools can truly thrive and provide the kind of education that every young adolescent deserves. The future of our country depends on it.